Α-Tocopherol attenuates NF-κB activation and pro-inflammatory cytokine IL-6 secretion in cancer-bearing mice. Issue 5 (5th August 2011) - Sharma, Renu; Vinayak, Manjula
Abstract : Cancer development and progression are closely associated with inflammation. NF-κB (nuclear factor κB) provides a mechanistic link between inflammation and cancer, and is a major factor controlling the ability of malignant cells to resist tumour surveillance mechanisms. NF-κB might also regulate tumour angiogenesis and invasiveness and the signalling pathways that mediate its activation provide attractive targets for new chemopreventive and chemotherapeutic approaches. ROS (reactive oxygen species) initiate inflammation by up-regulation of pro-inflammatory cytokines and therefore antioxidants provide a major defence against inflammation. α-Tocopherol is a lipid-soluble antioxidant. In addition to decreasing lipid peroxidation, α-tocopherol may exert intracellular effects. Hence, the aim of this study was to test the effect of α-tocopherol supplementation in cancer prevention via suppression of NF-κB-mediated pro-inflammatory cytokines. α-Tocopherol treatment significantly down-regulates expression, synthesis as well as secretion of pro-inflammatory cytokine IL-6 (interleukin-6) in cancerous mice. It also suppresses NF-κB binding to IL-6 promoter in liver leading to decreased secretion of IL-6 in serum. The regulation of the signalling pathway by α-tocopherol is found apart from its antioxidant capacity to reduce lipid peroxidation. Thus, the present study provides evidence for the hypothesis that besides the powerful free radical scavenging effects, α-tocopherol has genomic effects in down-regulation of pro-inflammatory cytokine and cancer prevention via the NF-κB-dependent pathway.